Beyond Traditional Models: Exploring the Synergy of Total Quality Management and Educational Excellence in Madrasah - Encu, Asep (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyze the implementation of transformative leadership in madrasahs, focusing on four main components: idealized influence, inspirational motivation, intellectual stimulation, and individual consideration. The approach used in this study is a qualitative method with a case study design. Data collection techniques were carried out through in-depth interviews with the madrasah principal, teachers, and several students, as well as direct observation. The data obtained were analyzed using thematic analysis techniques. The results of the study indicate that the madrasah principal has succeeded in acting as a role model who inspires, motivates, and supports innovation among teachers and students. The implementation of this leadership contributes to achieving better quality education, with a balance between academic achievement and student character development. This study provides implications that transformative leadership in madrasahs can improve the quality of education through the inspiration and innovation of the madrasah principal. However, limitations in decision-making participation and intellectual stimulation indicate the need for improvement in these aspects so that transformative leadership can optimally support the development of madrasahs.